Intrinsic motivation of college athletes and football players in Iceland: Effects of coaches’ leadership style and determinants of intrinsic motivation - Magnús Pálmi Gunnarsson 1992-; Hjörtur Þórisson 1992- (2017)
The purpose of this study was to address intrinsic motivation in two different samples of athletes in Iceland and assess variables that relate to or affect their intrinsic motivation. The first sample consisted of both male and female footballers from 21 teams in three different divisions in Iceland. The Sport Motivation Scale-6 (SMS-6) questionnaire was used to measure the football players’ intrinsic motivation. Results indicated that (a) football players in the top divisions report higher intrinsic motivation than football players in fourth division, (b) female football players report higher intrinsic motivation than their male counterparts in the top divisions, and (c) no relationship was found between football players’ age and intrinsic motivation. The second study assessed the relationship between leadership styles of coaches and intrinsic motivation of 50 male and 60 female college athletes from variety of sports at the University of Iceland. Additionally to SMS-6 questionnaire, researchers used Leadership Scale for Sports (LSS) to measure athletes’ perceived behavior of their coaches to see if there was any relationship between coaches’ leadership styles and athletes’ intrinsic motivation. Results from these combined questionnaires revealed that (a) democratic leadership styles of coaches and athletes’ intrinsic motivation is positively correlated, thus the more that athletes perceives their coaches to be democratic the higher the levels of intrinsic motivation, (b) athletes who perceives their coaches to show behavior of social support and positive feedback report higher intrinsic motivation, and (c) positive correlation between higher training and instruction behavior among coaches and athletes’ intrinsic motivation.